Pengaruh kebudayaan lokal terhadap pemahaman ajaran Islam di Indonesia - Andrianti, Elma Suci (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the influence of local culture on the understanding and practice of Islamic teachings in Indonesia. As a country with vast cultural diversity, Indonesia presents a unique context where Islamic teachings are often interpreted and practiced in harmony with local values. The research adopts a qualitative approach using case studies in various communities across regions such as Java, Aceh, and Sulawesi. The findings reveal that local culture influences the understanding of Islamic teachings through the adaptation of rituals, values, and religious symbols that align with traditional customs. This is reflected in practices such as selametan, Maulid traditions, and other cultural ceremonies, which blend Islamic nuances with local wisdom. The study concludes that the integration of local culture and Islam not only enriches the diversity of religious expression in Indonesia but also demonstrates the flexibility of Islamic teachings in responding to socio-cultural dynamics.